Efektivitas Suplementasi Temu Ireng (Curcuma Aeruginosa) Dalam Ransum Terhadap Kecernaan Bahan Kering Dan Kecernaan Bahan Organik Pada Kambing Jawarandu Jantan - FAIZ, HARUN; Muhtarudin, Muhtarudin; Erwanto, Erwanto; Tantalo, Syahrio (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2025)
This study aims to determine the effect of providing ginger ireng supplementation on dry matter digestibility and organic matter digestibility of male Jawarandu goats. This research was carried out in April 2024 - May 2024 at the Margo Lembu cage, Adijaya, Central Lampung. This research was carried out using a Completely Randomized Design (CRD) consisting of 4 treatments and 3 replications, using 12 male Jawarandu goats. The treatments used were P0: 100% basal ration, P1: 100% basal ration + 750mg temu ireng /head/day, P2: 100% basal ration + 1,500 mg temu ireng/head/day and P3: 100% basal ration + 2,250 mg ireng meeting/tail/day. The data obtained were analyzed using Analysis of Variance (ANOVA). Results of research on the effectiveness of supplementation of temu ireng (cucurma aeruginosa) in rations on dry matter digestibility (P0: 79.42%, P1: 80.98%, P2: 84.94% and P3: 83.34%) and organic matter digestibility ( P0: 73.41%, P1: 76.57 %, P2: 82.38% and P3: 78.43%). The conclusion of this study was that the treatment of curcuma ireng supplementation had no significant effect (P>0.05) on the digestibility of dry matter and the digestibility of organic matter. P2 treatment on dry matter digestibility and organic matter digestibility with the addition of a 1,500mg dose of temu ireng was the best treatment compared to other treatments because it was able to increase dry matter digestibility and organic matter digestibility of male Jawarandu goats.